Mitigation of the adverse effects of soil salinity in rice using exogenous proline and organic manure (Asian Journal of Medical and Biological Research, 2016)
Salinity causes cellular damage and limits crop productivity. Accumulation of organic compound is one of the major adaptive mechanisms for salinity tolerance in plants. The main objective of the present study was to mitigate the adverse effects of soil salinity in rice through organic amendments like proline and organic manure. The field experiments were conducted at the farmers field of Batiaghata upazilla under Khulna district with aman rice. The soil was silty clay loam having pH 7.2, EC 6.6 dS/m, CEC 26 meq/100 g soil and organic matter 0.84%. Rice variety BR 23 was used as a test crop. There were 15 treatment combinations with different doses of proline and organic manures. Recommended doses of N, P, K, S and Zn fertilizers were applied to all the experimental plots. Proline was applied as foliar spray at seedling and/or vegetative stages. Organic manures were added to soils during final land preparation. The experiments were laid out in a randomized complete block design with three replications. Significant reductions in growth and yield of rice were observed under saline conditions. Application of both proline and organic manures significantly increased growth, yield contributing characters, and grain and straw yields of rice under salinity conditions. There were no significant variations in growth and yield of rice due to use of different doses of proline and organic manure. Increased nutrient uptake and K+/Na+ ratio were observed in rice due to proline as well as organic manure application under saline conditions. The present study suggests that exogenous proline or organic manure confers tolerance to salinity in rice by increasing K+/Na+ ratio and nutrient uptake.Asian J. Med. Biol. Res. December 2015, 1(3): 478-486